(untitled) (Sociologisk Forskning, 2000)
Pitirim Sorokin: Suicide as a societal phenomenon Sorokin’s early work on suicide, published 1913, is heavily influenced by Durkheim. However, already at this stage the great sociologist-in-making is evident. There are important differences between Sorokin’s way of discussing the causes of suicide and that of Durkheim. In particular, Sorokin is aware of the specific features of Russia, including acute poverty, misery and hunger as well as social disruption. He suggests that those are important mechanisms in the suicide crisis of early 20th century Russia.